DESIGNING MARKETING CHANNELS: MULTIPLE MARKETING CHANNELS AT WINERY “MAČKOV PODRUM” - Đurić, Slađana; Stojiljkovic, Aleksandra (Journal of process management and new technologies, 2018)
Designing marketing channels in order to penetrate targeted market and to attain desired position in that market requires making various decisions related to the channel structure, selection of channel members and organization of activities that need to be performed in those channels in order to deliver the product/service to customers. This paper is about the process of making decisions involved in designing the marketing channels of the company. Seven phases of the Paradigm of the channel design decision are discussed. Winery “Mačkov podrum” from Irig, Vojvodina, is taken as the example of the company that successfully combines several channels to attain market presence and coverage.